2020
DOI: 10.3390/diagnostics10080573
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 and PR in Patients Treated with CDK4/6 Inhibitors: A Real-World Experience

Abstract: CDK4/6 inhibitors (CDK4/6i) are recommended in patients with estrogen receptor (ER)-positive, HER2-negative advanced breast cancer (ABC). Up to now, no prognostic biomarkers have been identified in this setting. We retrospectively analyzed the expression of progesterone receptor (PR) and Ki67, assessed by immunohistochemistry, in 71 ABC patients treated with CDK4/6i and analyzed the impact of these markers on progression-free survival (PFS). The majority of patients 63/71 (88.7%) received palbociclib, 4 (5.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…Meanwhile, Ki67 value was not indicated to be a prognostic factor for response to CDK4/6i in a series of prospective trials. Only 1 retrospective study reported that PFS was negatively affected by elevated Ki67 values (22). The key challenge in Ki67 research is the poor interlaboratory assay reproducibility due to the diversity in diagnosis kits and platforms being used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Ki67 value was not indicated to be a prognostic factor for response to CDK4/6i in a series of prospective trials. Only 1 retrospective study reported that PFS was negatively affected by elevated Ki67 values (22). The key challenge in Ki67 research is the poor interlaboratory assay reproducibility due to the diversity in diagnosis kits and platforms being used.…”
Section: Discussionmentioning
confidence: 99%
“…Also, retinoblastoma protein (Rb)-negative cases have been shown to have high Ki67 levels (21). In addition, Palleschi et al (22) revealed that the progressionfree survival (PFS) of patients with CDK4/6i and endocrine therapy was inversely related to Ki67 expression, but not to PR. Thus, studies concerning the predictive significance of Ki67 and PR for CDK4/6i are rare and controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the monarchE trial the authors found that high Ki67 levels (Ki67 ≥20%) showed benefit of abemaciclib and ET in the adjuvant setting for ER-positive, HER2- negative early-stage BC with high-risk features [17]. Although much effort has been exerted in the adjuvant setting, the prognostic benefit of Ki67 and PR expression to predict palbociclib efficacy in the metastatic setting is still not clear despite discussion in the literature [1, 4, 5]. Palleschi et al [1] showed that Ki67 can predict CDK4/6i + ET efficacy in metastatic BC but PR expression failed to show any benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib is the first selective inhibitor of the cyclin-dependent kinases CDK4 and CDK6 (CDK4/6i) and is widely used for HR+ metastatic BC. Following the success of palbociclib, CDK4/6i in combination with ET has become the standard therapy [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation